2014
DOI: 10.3390/ijms150610635
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metastases from Lung Cancer Show Increased Expression of DVL1, DVL3 and Beta-Catenin and Down-Regulation of E-Cadherin

Abstract: The susceptibility of brain to secondary formation from lung cancer primaries is a well-known phenomenon. In contrast, the molecular basis for invasion and metastasis to the brain is largely unknown. In the present study, 31 brain metastases that originated from primary lung carcinomas were analyzed regarding over expression of Dishevelled-1 (DVL1), Dishevelled-3 (DVL3), E-cadherin (CDH1) and beta-catenin (CTNNB1). Protein expressions and localizations were analyzed by immunohistochemistry. Genetic alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 55 publications
1
36
1
Order By: Relevance
“…Two WNT regulated genes, Lef1 and HoxB9, were specifically implicated in metastatic cell invasiveness and colony formation [20]. Brain metastases in patients show up-regulation of WNT target genes [94]. …”
Section: The Final Stage Of the Metastatic Cascade: Organ Colonizationmentioning
confidence: 99%
“…Two WNT regulated genes, Lef1 and HoxB9, were specifically implicated in metastatic cell invasiveness and colony formation [20]. Brain metastases in patients show up-regulation of WNT target genes [94]. …”
Section: The Final Stage Of the Metastatic Cascade: Organ Colonizationmentioning
confidence: 99%
“…DVL-1 and DVL-3 showed over expression in brain metastasis in 87.1% and 90.3% of samples respectively. Nuclear staining was observed in 54.8% of cases for DVL-1 and 53.3% for DVL-3, and when DVL-1 and DVL-3 were up-regulated there was a significant increase in the number of cases with nuclear beta-catenin [163]. …”
Section: Cancer Associationsmentioning
confidence: 99%
“…Although SCLC is unique in that it has a high propensity for brain metastasis, limited attention has been paid to SCLC brain metastases. Recently, a clinical study indicated that high expression of chemokine receptor-4 may correlate with SCLC brain metastasis (8), and the altered expression of Dishevelled-1, Dishevelled-3, E-cadherin, and b-Catenin are present in brain metastases, which suggests that Wnt signaling is important in SCLC metastasis to the brain (9). Our previous study revealed that a role of the Rho/Rho-associated protein kinase signaling pathway in human brain microvascular endothelial cells (HBMECs) during SCLC cells migration across the BBB (10).…”
mentioning
confidence: 99%